Ebstein Anomaly and Sudden Childhood Death. Issue 3 (20th September 2017) - Freeman, Amanda; Byard, Roger W.
Abstract: A 13‐year‐old girl is reported who died suddenly and unexpectedly in her sleep from previously undiagnosed Ebstein anomaly. At autopsy, there was dilatation of the right atrium with marked dilatation of the right auricle and apical displacement of the tricuspid valve into the right ventricular cavity with atrialization of the upper portion of the right ventricle. There were also prominent dysplastic changes in both the septal and posterior leaflets of the tricuspid valve with thickening of the valve and fusion of leaflets to the wall of the ventricle. Histology of the myocardium showed focal, minor microscopic areas of interstitial fibrosis with marked fibrous dysplasia and thickening of the tricuspid valve. Lethal arrhythmias occur in this condition because of the geographical relationship of the conduction system to the abnormal anatomical structures. As adolescents who died suddenly are often minimally symptomatic, cases will rarely present de novo to forensic autopsy.